Cross-Reactivity between COX-2 Inhibitors in Patients with Cross-Reactive Hypersensitivity to NSAIDs - Gültuna Selcan; Gümüşburun Reyhan; Bavbek Sevim (Journal of Public Health International, 2022)
The safety of cyclooxygenase (COX)-2 inhibitors has been tested in patients who had cross-reactive hypersensitivity reactions (HSRs) to nonsteroidal anti-inflammatory drugs (NSAIDs). However, these studies have been mainly done before the current classification of NSAID hypersensitivity and cross-reaction between COX-2 inhibitors has been rarely reported.We aimed to assess tolerability of COX-2 inhibitors and to evaluate the cross-reactivity between them in cross-reactive phenotype of NSAID hypersensitivity. The diagnosis was based on clinical features, reliable history of HSRs to at least two chemically different NSAIDs, and/or positive provocation tests with implicated NSAIDs in 151 patients. Single-blind, oral challenges with 1/4 and 3/4 divided doses of placebo, nimesulide, meloxicam, and celecoxib, as COX-2 inhibitors, were performed. The most common cross-reactive phenotype was NSAID-induced urticaria/angioedema (56.3%). Positive reactions to meloxicam, nimesulide, and celecoxib challenges were observed in 23/140 (16.4%), 7/33 (21.2%), and none of six patients, respectively. Overall, 24 patients were tested with two, one was tested with three COX-2 inhibitors. Six (31.6%) of 19 patients with meloxicam intolerance reacted to nimesulide provocation. Nimesulide, meloxicam, and celecoxib appeared safe alternatives in cross-reactive phenotypes of NSAID hypersensitivity. Although celecoxib has the most favorable tolerability, cross-reactivity among COX-2 inhibitors seems to be possible.
Keywords: Aspirin hypersensitivity